Optimization of Legal Protection for Consumers in Online Buying and Selling Transactions based on Consumer Protection Law - M. Sunandar Yuwono; Evita Isretno Israhadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Consumer protection in e-commerce transactions in Indonesia faces significant challenges due to the lack of specific regulations that clearly define the responsibilities of digital platforms. Law Number 8 of 1999 concerning Consumer Protection (UUPK) serves as the primary legal framework, but it has not adequately addressed the complexities of digital transactions, leading to legal uncertainty in resolving disputes and safeguarding consumer rights. This gap in the law leaves consumers vulnerable, as their rights are not clearly protected in the digital environment. One of the main issues is the low level of consumer legal literacy in Indonesia, which exacerbates the problem. Many consumers are unaware of their rights or how to enforce them, making it difficult for them to seek redress in case of problems with e-commerce transactions. This lack of understanding creates an environment where consumers are often left without proper recourse when facing issues such as faulty products, delayed deliveries, or breaches of personal data security. This study aims to identify the barriers to consumer protection in e-commerce and propose solutions to address these challenges. The study suggests that more comprehensive and adaptive regulations are needed to define the responsibilities of e-commerce platforms clearly. These regulations should include effective complaint mechanisms, stronger consumer data protection policies, and a framework for resolving disputes quickly and transparently. Additionally, the study emphasizes the need for stricter supervision and more robust law enforcement to ensure that digital trading platforms comply with consumer protection laws. The findings highlight the importance of creating a safe, fair, and trusted digital trading ecosystem in Indonesia, where consumers feel secure and are empowered to demand their rights. By implementing these recommendations, Indonesia can improve consumer protection in the digital economy, ultimately fostering a more sustainable and transparent e-commerce environment.